Rising inequality in mortality among working-age men and women in Sweden: a national registry-based repeated cohort study, 1990–2007. Issue 12 (20th August 2014) - Kondo, Naoki; Rostila, Mikael; Åberg Yngwe, Monica
Abstract : Background: In the past two decades, health inequality has persisted or increased in states with comprehensive welfare. Methods: We conducted a national registry-based repeated cohort study with a 3-year follow-up between 1990 and 2007 in Sweden. Information on all-cause mortality in all working-age Swedish men and women aged between 30 and 64 years was collected. Data were subjected to temporal trend analysis using joinpoint regression to statistically confirm the trajectories observed. Results: Among men, age-standardised mortality rate decreased by 38.3% from 234.9 to 145 (per 100 000 population) over the whole period in the highest income quintile, whereas the reduction was only 18.3% (from 774.5 to 632.5) in the lowest quintile. Among women, mortality decreased by 40% (from 187.4 to 112.5) in the highest income group, but increased by 12.1% (from 280.2 to 314.2) in the poorest income group. Joinpoint regression identified that the differences in age-standardised mortality between the highest and the lowest income quintiles decreased among men by 18.85 annually between 1990 and 1994 (p trend=0.02), whereas it increased later, with a 2.88 point increase per year (p trend <0.0001). Among women, it continuously increased by 9.26/year (p trend <0.0001). In relative terms, age-adjusted mortality rate ratios showed a continuous increase in both genders. Conclusions: Income-based inequalities among working-age male and female Swedes have increased since the late 1990s, whereas in absolute terms the increase was less remarkable among men. Structural and behavioural factors explaining this trend, such as the economic recession in the early 1990s, should be studied further.